The efficacy of relaxation therapy as adjunctive therapy on physical function, symptoms and medication intake in patients with knee osteoarthritis - Elias, Azlina (2013)
Osteoarthritis is the commonest arthritis especially in the elderly. Despite the usage of pharmacotherapy in managing this disease, psychological therapy such as Guided Imagery Relaxation (GIR) has been shown to reduce stress and pain in various types of chronic diseases. The objective of our study is to determine the efficacy of relaxation therapy as adjunctive therapy on symptoms, physical functions and analgesic consumption in patients with primary knee osteoarthritis. A randomized controlled trial with two arm parallel comparative study for relaxation therapy versus control among patient with knee osteoarthritis was carried out to see the its efficacy in improving pain, symptoms and physical function. Sixty knee osteoarthritic patients were recruited for this study. Knee injury and Osteoarthritis Outcome Score (KOOS) was used to measure pain, symptoms, sports and recreational, activity of daily living and health related quality of live scores among these patients. Analgesic consumption was calculated throughout the intervention period to see the difference between intervention and control groups.The treatment consists of listening to 12 minutes MP3 with prerecorded Guided Imagery with Relaxation Therapy at least once per day for the duration of 8 weeks. ANCOVA test was used to compare the score differences between intervention and control groups after the intei’vention. A total of sixty patients enrolled into the study however only 59 patients completed the study (98.3%). The mean age of the patients is 52.2(7.08).There were significant improvements of pain (p<0.004), activity of daily living (p<0.02), sport score (p<0.005), and quality of life score (p<0.01) in intei’vention group compared to control group. The analgesic score as lower in the intei’vention group, however it was not statistically significant. Guided imagery with Relaxation therapy has shown positive effects in managing patients with knee osteoarthritis. This intei’vention has significantly reduced pain, improve activity of daily living and also health related quality of life. This result justifies further investigations of Guided imagery with Relaxation therapy as self-management in patients with knee osteoarthritis.